2017
DOI: 10.1097/prs.0000000000003235
|View full text |Cite
|
Sign up to set email alerts
|

Is Enhanced Recovery the New Standard of Care in Microsurgical Breast Reconstruction?

Abstract: Background Enhanced recovery pathways (ERPs) have been shown to aid in patient recovery and improve outcomes in many surgical settings. At present, there is limited data available regarding the use and feasibility of ERPs for patients undergoing microsurgical breast reconstruction. We sought to assess patient outcomes before and after the introduction of an ERP that was adopted by multiple surgeons at a single cancer center. Methods A multidisciplinary ERP was developed for patients undergoing deep inferior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
146
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(159 citation statements)
references
References 31 publications
(30 reference statements)
4
146
3
1
Order By: Relevance
“…As demonstrated in this study, 91.3% of patients included in this study did not require any PCA postoperatively. This compares favorably with the results of Afonso et al and Batdorf et al who reported that following implementation of an ERAS pathway only 21% and 20% of their patients used postoperative PCA, respectively …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As demonstrated in this study, 91.3% of patients included in this study did not require any PCA postoperatively. This compares favorably with the results of Afonso et al and Batdorf et al who reported that following implementation of an ERAS pathway only 21% and 20% of their patients used postoperative PCA, respectively …”
Section: Discussionsupporting
confidence: 88%
“…In addition to the small percentage of patients requiring postoperative PCA and the lower total postoperative OME use when compared to our previous report, median patient‐reported pain scores were lower in the present study, thus, indicating improved postoperative analgesia, not just based on objective (ie, OME) but also subjective data. Adequate postoperative analgesia is, furthermore, reflected by a mean LOS of 3.5 days in our patient cohort, which compares favorably with other reports following successful implementation of ERAS protocols . Of note, a recent study by Jablonka et al reported an even shorter LOS following introduction of TAP blocks with liposomal bupivacaine, namely an average of 2.65 days …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Στην Ελλάδα δεν έχει εκδοθεί από κάποιο επίσηµο κρατικό φορέα πρωτόκολλο ERAS για την άµεση αποκατάσταση µε διατατήρες µετά από µαστεκτοµή. Παράλληλα, σε αρκετά ιδιωτικά νοσοκοµεία εφαρµόζονται παρόµοια προγράµµατα για την αποκατάσταση µετά από µαστεκτοµή µε µεγάλη µείωση της συνολικής µέσης διάρκειας νοσηλείας από 3,6 ηµέρες πριν από την εφαρµογή του προγράµµατος ERAS σε 0 (αυθηµερόν εξιτήριο) έως 1,2 ηµέρες (Mertz et al 2013, Dumestre et al 2017, Afonso et al 2017.…”
unclassified